The Effect of HIV/AIDS Scourge on Food Security in Nyabbani Subcounty, Kitagwenda District. - Ainembabazi, Docus (Kabale University, 2023)
The purpose of this research was to assess, analyze, find out, and gather the effect of HIV/AIDS scourge on food security in Nyabbani sub-county, Kitagwenda district.